2021
DOI: 10.1177/1742271x21995217
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an ultrasound bladder scanner in prostate radiotherapy: A validation study and analysis of bladder filling variability

Abstract: Introduction During prostate radiotherapy treatment, it is important to ensure the position of the bladder and prostate is consistent between treatments. The aim of this study was to provide a quantitative basis for incorporating ultrasound bladder volume estimates into local practice for prostate radiotherapy. Methods Agreement between bladder volume estimates obtained using computed tomography (CT) and ultrasound was assessed. Analysis of bladder volumes between planning and treatment scans was used to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Yoon et al [ 19 ] and Chang et al [ 7 ] conducted separate studies involving 20 patients with rectal cancer receiving RT, demonstrating a strong correlation between BV measured by BioCon-700 (Mcube Technology, Seoul, Korea) and CT ( r = 0.87, 0.93). Claxton et al [ 20 ] and Smith et al [ 6 ] measured BV in 20 patients with cervical/endometrial cancer and 19 patients with prostate cancer treated with RT, respectively, using BioCon-700 and CT, and obtained similar strong correlations. Stam MR et al [ 14 ] and O’Doherty et al [ 21 ] enrolled 26 and 41 patients with prostate cancer, respectively, and showed a strong correlation between BV measured by BladderScan BVI3000(Verathon Medical Europe, Washington State, USA) and CT ( r = 0.95, r = 0.88).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Yoon et al [ 19 ] and Chang et al [ 7 ] conducted separate studies involving 20 patients with rectal cancer receiving RT, demonstrating a strong correlation between BV measured by BioCon-700 (Mcube Technology, Seoul, Korea) and CT ( r = 0.87, 0.93). Claxton et al [ 20 ] and Smith et al [ 6 ] measured BV in 20 patients with cervical/endometrial cancer and 19 patients with prostate cancer treated with RT, respectively, using BioCon-700 and CT, and obtained similar strong correlations. Stam MR et al [ 14 ] and O’Doherty et al [ 21 ] enrolled 26 and 41 patients with prostate cancer, respectively, and showed a strong correlation between BV measured by BladderScan BVI3000(Verathon Medical Europe, Washington State, USA) and CT ( r = 0.95, r = 0.88).…”
Section: Discussionmentioning
confidence: 85%
“…Bladder volume (BV) is a significant factor in determining the target volume for cervical/cervical cancer [ 3 , 4 ], prostate cancer [ 5 , 6 ], and rectal cancer [ 7 , 8 ]. Variations in BV among treatment fractions have been observed; Ahmad et al [ 4 ] found an average reduction of 71% in bladder capacity among patients with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation